TANGGUNG JAWAB E-MARKETPLACETERHADAP KONSUMEN(Studi Kasus Phising di PT. Shopee Indonesia) - Nur Rizkiah Hasanah (2022)
Phishing cases that occurred on the shopee.co.id site resulted in several consumers experiencing losses, this could be due to the weak understanding of consumers regarding the Phishing cases that occurred. Lack of accuracy of consumers in accessing links so that it can plunge consumers into losses. For this reason, this thesis discusses the responsibility of e-marketplaces to consumers for Phishing cases that occurred at PT. Shopee Indonesia and Shopee's role in tackling phishing cases that can harm Shopee users. The research method used in this study is normative empirical juridical by conducting field research (field research) to obtain data and analyze related cases. in detail. The types of data used in this study are primary data and secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Based on the results of later research, it can be concluded that the principles of Shopee's responsibility for phishing cases and regarding the role of shopee to prevent phishing, in this case there is a limitation of responsibility in it which is also phishing, this is contrary to Article 15 paragraph 1 UU ITE, Article 12 PP PSTE, Article 31 PP PSTE, Article 4a UUPK, Article 7 UUPK and Article 18 paragraph 1 UUPK.